Patterns of Care for Locally Advanced Pancreatic Adenocarcinoma Using the National Cancer Database. Issue 7 (August 2017) - Amini, Arya; Jones, Bernard L.; Stumpf, Priscilla; Leong, Stephen; Lieu, Christopher H.; Weekes, Colin; Davis, S. Lindsey; Messersmith, Wells A.; Purcell, William T.; Ghosh, Debashis; Schefter, Tracey; Goodman, Karyn A.
Abstract : Objectives: The role of radiotherapy (RT) in locally advanced pancreatic cancer (LAPC) is uncertain. This study examines patterns of care and survival outcomes of LAPC undergoing chemotherapy alone versus chemotherapy plus RT (C + RT). Methods: The National Cancer Database was queried for nonmetastatic LAPC patients who received chemotherapy alone or C + RT. Results: Of the 13, 695 patients included, 5306 underwent chemotherapy alone and 4971, C + RT. Use of C + RT declined from 2003 to 2011 (73%–53%), whereas chemotherapy alone increased. Of those receiving RT, rates of intensity-modulated radiotherapy (IMRT) increased (27%–72%), whereas 3-dimensional (3D) RT decreased (73%–28%). Unadjusted 1-year overall survival (OS) was longer for versus chemotherapy (45.6% vs 38.7%), as was 2-year OS (12.9% vs 11.9%) (hazard ratio, 0.88; 0.85–0.91; P < 0.001). Under multivariate analysis, C + RT was associated with improved OS (hazard ratio, 0.84; 0.81–0.87; P < 0.001). On subgroup analysis comparing C + IMRT, C + 3D RT, and chemotherapy alone, 1-year OS was 49.1%, 45.1%, and 38.7%, and 2-year OS was 13.1%, 11.6%, and 11.9% accordingly. Conclusions: Utilization of RT in LAPC is decreasing, whereas chemotherapy alone is increasing. Of patients undergoing RT, rates of IMRT are increasing. Whereas C + IMRT appeared to be associated with improved OS compared with chemotherapy alone, 3D RT was not. Abstract : Supplemental digital content is available in the text.